Using TikTok English Song Lyrics to Improve Pronunciation Among Junior High School Students - Nurafifah, Aulia; Ridwan, Ridwan; Junaedi, Ahmad; Ikhsan, Ikhsan (Innovations in Language Education and Literature, 2025)
This study explores the effectiveness of using English song lyrics from TikTok as a medium to improve students’ pronunciation skills. Employing a quasi-experimental design, the research involved 38 eighth-grade students at SMP Negeri Limboro in the 2024/2025 academic year. Participants were divided into two groups: an experimental group received instruction using selected TikTok English song lyrics, while the control group was taught using conventional methods. Data were collected through pre-tests, post-tests, and student questionnaires. Statistical analysis using SPSS showed a significant improvement in the pronunciation scores of the experimental group compared to the control group. The mean N-Gain score of 58.4% indicates a moderate level of effectiveness. Furthermore, students’ responses to the questionnaire demonstrated positive perceptions toward the use of English songs on TikTok as a learning tool. The findings suggest that integrating digital media, particularly short-form social platforms like TikTok, can enhance pronunciation instruction and motivate learners. This study contributes to the growing field of digital-assisted language learning and provides insights for teachers seeking innovative methods to support pronunciation development in EFL classrooms.